Calidad de la lonchera escolar y su relación con el estado nutricional en niños preescolares de 3 a 5 años de escuela de Educación Básica España, Puebloviejo Los Ríos, segundo semestre octubre 2018 – abril 2019 - Valero Valero, Gianella Lissette (2019)
In the present investigative report, the relationship of the school lunch box in the nutritional status of the children of the Spanish Basic Education School was analyzed, for which both general and specific objectives were set, seeking in this way to address the problem that deepens the childhood today is the formation of bad eating habits that generates, that currently there is a high rate of childhood obesity, it is so in the educational institution was obtained as there are 9 children with overweight, 11 with obesity and 12 with severe malnutrition all this added to reflect 40% of the population of children between 3 - 5 years of age in addition to it was known that the food consumption of preference that parents send in school lunch box is mainly made up of junk food in 57% and sweetened cookies by 43% and if we add to this that 66% of the lunch boxes are packed with high sugar content juices the school lunchbox has an overload of sugar and does not maintain a nutritional balance, for this reason it was concluded that it is necessary to conduct nutrition education and awareness campaigns for the formation of better eating habits and also the realization of a guide to improve the production of a lunchbox school nutrition and quality.